PENGARUH LATIHAN PUSH UP TERHADAP HASIL MEMANAH JARAK 30 METER ATLET PANAHAN PUTRA PPLM DEVISI STANDAR BOW - Yenni, Fitri Rahma; ', Ramadi; Agust, S.Pd, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: the problem in this research is the lack of ability of muscle strength and endurance in athletes archeryson PPLMdivision. bowstandard By the time athletes perform archery test distance of 30 meters only two athletes who have archery scores 203-250, based on the norm otherwise lacking. The shape of this research is the experimental treatment (Experimental). The independent variable was exercise Push Up (X) while the dependent variable is the practice of archery within 30 meters (Y). With thetechnique total sampling is a sample of 6 people. Data were obtained and collected through the initial test and final test before and after the 30-meter archery exercises aimed at improving the ability of archery distance of 30 meters. Using the 30-meter tesmemanah instrument that aims to measure the strength of pull and push. After that, the data is processed with statistical, normality test withtest lilifors at significant level α (0.05). The hypothesis is the effect of exercise push up against the results of archery distance of 30 meters. Based on the analysis of statistical data, there are an average Pree test of 265.83andaverage post-test of 305.83, then the data is otherwise normal. Based on t test analysis produces Tcalculated at 10.756 and Ttable at 1,943, meaning Tarithmetic> Ttable. Thus, there Effect of Exercise Push Up Against Result Athletes Archery Archery Distance 30 Meter Men PPLMDivision. Standard BowKeywords: Push Up, Archery Distance 30 Meters